Fiber-reinforced polymer cement mortar composition and mortar thereof

JP7638742B2Active Publication Date: 2025-03-04TAIHEIYO MATERIALS CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021043107
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-17
Publication Date
2025-03-04
Estimated Expiration
2041-03-17

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、繊維の分散性に優れ、且つ、施工性、初期から長期にかけての強度発現性に優れる繊維補強ポリマーセメントモルタル組成物及びそのモルタルを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638742000003
    Figure 0007638742000003
  • Figure 0007638742000001
    Figure 0007638742000001
  • Figure 0007638742000002
    Figure 0007638742000002
Patent Text Reader

Abstract

To provide a fiber-reinforced polymer cement mortar composition that has excellent fiber dispersibility, and excellent workability and from early to long term strength development.SOLUTION: Provided is a fiber-reinforced polymer cement mortar composition that contains cement, pozzolan substance, metal fiber, and polymer for cement, and in which the contained amount of the pozzolan substance is 2 to 38 pts.mass and the contained amount of the metal fiber is 2 to 38 pts.mass for 100 pts.mass of the cement, and the metal fiber has a substantially straight portion and a deformed portion that is formed by bending from at least one end of the metal fiber so as to form an angle with the substantially straight portion.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fiber-reinforced polymer cement mortar composition and a mortar thereof. [Background technology]

[0002] Cracks can occur in concrete structures (for example, floor slabs, walls, and ceilings of reinforced concrete slabs, precast concrete slabs, and intermediate floor slabs of box culverts) due to fatigue and drying shrinkage. When the width of a crack increases due to the progression of this type of deterioration or the cracks being rubbed together, deterioration factors such as water and chloride ions can penetrate into the concrete structure. This results in corrosion of the reinforcing bars embedded in the concrete structure. If damage caused by cracks in a concrete structure is left unattended, the reinforcing bars inside will eventually corrode, causing cross-sectional defects and making it impossible to maintain the safety of the structure. For this reason, preventive measures are taken, such as repair work on deteriorated areas and the use of highly durable materials.

[0003] Polymer-cement mortar and polymer-cement concrete are widely used as repair and reinforcement materials, and there is a demand for further improvement in their durability. For example, the use of fibers in polymer-cement mortar has been proposed to improve crack resistance and bending strength.

[0004] Patent Document 1 discloses a premixed highly tough polymer cement mortar material containing cement, fine aggregate, re-emulsified powdered resin, a clay mineral-based thixotropic agent, and high-strength organic short fibers. Patent Document 2 discloses a polymer cement composition containing cement, water, aggregate, a polymer, and high-strength short fibers having a specific tensile strength. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2007-269537 A [Patent Document 2] JP 2010-105831 A Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, efforts have been made to increase the strength of mortar and concrete to meet the demands for ultra-high rise, large scale, and high durability of architectural and civil engineering structures, and similar demands are being made for repair and reinforcement materials. However, polymer cement mortar containing fibers has a problem in increasing the strength of mortar due to the inclusion of polymer components and fibers, and it has been difficult to achieve compatibility with the mixability of fibers. In addition, when the time available for construction is limited, such as in partial repair work on structures such as roads and railways, repair materials that are easy to mix and quickly develop strength after construction are required.

[0007] Therefore, an object of the present invention is to provide a fiber-reinforced polymer cement mortar composition which is excellent in fiber dispersibility, workability, and initial and long-term strength development, and a mortar made from the composition. [Means for solving the problem]

[0008] As a result of intensive research into the above-mentioned problems, the present inventors have found that by blending specific amounts of metal fibers having specific shapes and a pozzolanic substance, it is possible to obtain a fiber-reinforced polymer cement mortar composition and a mortar made from the same that have excellent fiber dispersibility, workability, and excellent initial and long-term strength development.

[0009] That is, the present invention relates to the following [1] to [7]. [1] A fiber-reinforced polymer cement mortar composition comprising cement, a pozzolanic substance, metal fibers, and a polymer for cement, the pozzolanic substance being contained in an amount of 2 to 38 parts by mass and the metal fibers being contained in an amount of 2 to 38 parts by mass per 100 parts by mass of the cement, the metal fibers having a substantially straight portion and a deformed portion formed by bending at least one end of the metal fibers so as to form an angle with the substantially straight portion. [2] The fiber-reinforced polymer cement mortar composition according to [1], wherein the length of the approximately straight portion accounts for 50 to 95% of the total length of the metal fiber, and the deformed portion is formed by bending each of both ends of the metal fiber so as to form an angle of 30 to 160 degrees with the approximately straight portion. [3] The fiber-reinforced polymer cement mortar composition according to [1] or [2], further comprising calcium aluminates and gypsums. [4] The fiber-reinforced polymer cement mortar composition according to any one of [1] to [3], wherein the content of the polymer for cement is 0.5 to 18 parts by mass, calculated as solid content, per 100 parts by mass of the cement. [5] The fiber-reinforced polymer cement mortar composition according to any one of [1] to [4], wherein the metal fibers have an aspect ratio of 25 to 150. [6] The fiber-reinforced polymer cement mortar composition according to any one of [1] to [5], further comprising an expansive agent. [7] A fiber-reinforced polymer cement mortar comprising the fiber-reinforced polymer cement mortar composition according to any one of [1] to [6] and water, the water content being 20 to 55 parts by mass per 100 parts by mass of the cement. Effect of the Invention

[0010] According to the present invention, it is possible to provide a fiber-reinforced polymer cement mortar composition having excellent fiber dispersibility, workability, and excellent initial and long-term strength development, and a mortar made from the same. [Brief description of the drawings]

[0011] [Figure 1] 1(a), (b), (c), (d), (e) and (f) are schematic diagrams illustrating the shapes of metal fibers to be blended in the fiber-reinforced polymer cement mortar composition according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Each drawing is a schematic diagram, and the size of each component is not limited to those shown in the drawings.

[0013] The fiber-reinforced polymer cement mortar composition of the present embodiment contains cement, a pozzolanic substance, metal fibers, and a cement polymer, and contains 2 to 38 parts by mass of the pozzolanic substance and 2 to 38 parts by mass of the metal fibers relative to 100 parts by mass of cement. The metal fibers have a substantially straight portion and a deformed portion formed by bending at least one end of the metal fibers at an angle to the substantially straight portion.

[0014] Various types of cement can be used, including, for example, various types of Portland cement such as normal, early strength, super early strength, low heat and medium heat, ecocement, rapid hardening cement, etc. As the cement, normal Portland cement and early strength Portland cement are preferred from the viewpoint of easily achieving both early hardening property and fluidity. One type of cement may be used alone, or two or more types may be used in combination.

[0015] Examples of the pozzolanic substance include various fly ashes described in JIS A 6201:2015, and silica fume, slag powder, and amorphous aluminosilicate described in JIS A 6207:2016. From the viewpoint of being more excellent in long-term strength development and workability, silica fume and amorphous aluminosilicate are preferable as the pozzolanic substance. One type of pozzolanic substance may be used alone, or two or more types may be used in combination.

[0016] The content of the pozzolanic substance is 2 to 38 parts by mass relative to 100 parts by mass of cement. If the content of the pozzolanic substance is outside the above range, sagging of the mortar occurs, reducing workability, and the dispersibility of the metal fibers is also reduced. From the viewpoint of more easily achieving both initial and long-term strength development, the content of the pozzolanic substance is preferably 5 to 35 parts by mass, and more preferably 8 to 30 parts by mass, relative to 100 parts by mass of cement. From the viewpoint of further improving long-term strength development, the fineness of the pozzolanic substance is preferably 5 to 35 parts by mass, and more preferably 8 to 30 parts by mass, relative to 100 parts by mass of cement. 2 / g or more, and 2 The fineness of the pozzolanic substance is preferably 30 m / g or more in terms of BET specific surface area. 2 It is preferable that the molecular weight is not more than 1 / g.

[0017] Fig. 1 is a schematic diagram showing the shape of a metal fiber 10 according to this embodiment. The metal fiber 10 is composed of a substantially straight portion 1 and a deformed portion 2 formed by bending at least one end of the metal fiber 10 at an angle A with the substantially straight portion 1. As shown in Fig. 1, the angle A is the angle between the substantially straight portion 1 and a line connecting the point where the bending of the metal fiber 10 begins (start point 3) and the end of the metal fiber 10 included in the deformed portion 2 (end point 4).

[0018] The length of the approximately straight portion 1 is preferably 50 to 95%, more preferably 60 to 94%, and even more preferably 70 to 93% of the total length of the metal fibers 10. When the length of the approximately straight portion 1 is within the above range, the kneadability and workability of the mortar are further improved.

[0019] The shape of the deformed portion 2 is not particularly limited. The deformed portion 2 may be linear as shown in FIG. 1(a) or curved as shown in FIG. 1(b). The deformed portion 2 may be further folded in the middle. For example, the deformed portion 2 may be further folded once in the middle as shown in FIG. 1(c), or may be further folded three times in the middle as shown in FIG. 1(d). Even if the deformed portion 2 has a bend in the middle, the start point 3 of the deformed portion 2 is a point where the deformed portion 2 is in contact with the approximately straight portion 1, and the end point 4 is an end of the metal fiber 10 included in the deformed portion 2. The angle of the bend in the middle of the deformed portion 2 is not particularly limited. The metal fiber 10 may have a plurality of deformed portions 2. For example, the metal fiber 10 may have deformed portions 2 at both ends as shown in FIG. 1(e), or may have two deformed portions 2 at one end of the metal fiber 10 as shown in FIG. 1(f). From the viewpoint of further reducing dripping of mortar and improving workability, it is preferable that the metal fiber 10 has a deformed portion 2 at each end of the metal fiber 10 and is further folded one or more times along the way of the deformed portion 2, and it is more preferable that the ends of the deformed portion 2 are folded once along the way in a direction away from each other so as to be parallel to the approximately straight portion 1 (Figure 1(e)).

[0020] The angle A is preferably 30 to 160 degrees, more preferably 50 to 160 degrees, even more preferably 70 to 160 degrees, even more preferably 90 to 150 degrees, and most preferably 120 to 150 degrees. When the angle A is within the above range, the workability of the mortar is further improved. When the metal fiber 10 has multiple deformed portions 2, the respective angles A may be the same or different.

[0021] The total length of the metal fibers 10 is preferably 15 to 50 mm, more preferably 20 to 45 mm, and even more preferably 25 to 40 mm. If the total length of the metal fibers 10 is within the above range, the kneadability and workability of the mortar are further improved.

[0022] The aspect ratio (total length / diameter) of the metal fibers 10 is preferably 25 to 150, more preferably 30 to 100, and further preferably 40 to 65. When the aspect ratio is within the above range, the kneadability and workability of the mortar are further improved, and sagging is less likely to occur.

[0023] The metal fibers 10 are not particularly limited as long as they are made of metal, and examples thereof include steel fibers, stainless steel fibers, amorphous metal fibers, and fibers whose surfaces have been subjected to chemical or physical treatment. From the viewpoint of achieving both the kneadability and hardening properties of the mortar, steel fibers are preferred as the metal fibers 10. The metal fibers 10 may be used alone or in combination of two or more types.

[0024] The content of the metal fibers 10 is 2 to 38 parts by mass relative to 100 parts by mass of cement. If the content of the metal fibers 10 is outside the above range, the dispersibility and strength expression of the metal fibers 10 decrease. From the viewpoint of easily achieving both the dispersibility and strength expression of the metal fibers 10, the content of the metal fibers 10 is more preferably 4 to 30 parts by mass, and further preferably 5 to 25 parts by mass, relative to 100 parts by mass of cement.

[0025] The polymer for cement is preferably a polymer specified in JIS A 6203:2015 "Polymer dispersions and re-emulsified powdered resins for cement admixture". Examples of such polymers for cement include polymer dispersions and re-emulsified powdered resins. Examples of polymer dispersions include synthetic rubbers such as styrene butadiene rubber (SBR); natural rubbers; rubber asphalts; ethylene vinyl acetates; acrylic esters; and resin asphalts. Among them, the polymer dispersions are preferably synthetic rubbers, ethylene vinyl acetates, and acrylic esters, and more preferably synthetic rubber latex, polyacrylic esters, and ethylene vinyl acetates. Examples of re-emulsified powdered resins include synthetic rubbers such as styrene butadiene rubber; acrylic esters; ethylene vinyl acetates; vinyl acetate / vinyl versatate esters; vinyl acetate / vinyl versatate / acrylic esters. As the polymer for cement, a polymer dispersion may be used, a re-emulsified powdered resin may be used, or a polymer dispersion and a re-emulsified powdered resin may be used in combination.

[0026] Among the polymers for cement, a polymer dispersion and / or a re-emulsified powder resin of styrene-butadiene rubber is preferred from the viewpoint of further improving adhesion to concrete and dimensional stability. Styrene-butadiene rubber is a type of synthetic rubber obtained by copolymerizing styrene and butadiene, and the quality can be appropriately adjusted by adjusting the styrene content and the amount of vulcanization. For cement admixture, those with a bound styrene content of 50 to 70 mass% are often used from the viewpoint of improving stability and adhesion. The polymers for cement may be used alone or in combination of two or more.

[0027] The content of the polymer for cement is preferably 0.5 to 18 parts by mass, more preferably 1 to 13 parts by mass, and even more preferably 1.5 to 8 parts by mass, in terms of solid content, relative to 100 parts by mass of cement. If the content of the polymer for cement is within the above range, better workability, dimensional stability, and higher adhesion to concrete are likely to be obtained.

[0028] The fiber-reinforced polymer cement mortar composition of the present embodiment may contain calcium aluminates, gypsum, fine aggregate, expansive agents, water reducing agents, setting retarders, and the like in addition to the above components.

[0029] The fiber-reinforced polymer cement mortar composition contains calcium aluminates, which provide excellent rapid hardening properties. Calcium aluminates include CaO, C, Al, 2 O 3 A, Na 2 O, N, and Fe 2 O 3 When expressed as F, C 3 A, C 2 A, C 12 A 7 , CA, or CA 2 Calcium aluminate, C, having a mineral composition indicated as 4 Calcium aluminoferrite, which is indicated as AF, and calcium aluminate in which halogens are dissolved or substituted 3 A 3 ·CaF 2 Or C 11 A 7 ·CaF 2 Calcium haloaluminates, including calcium fluoroaluminates, denoted as C, etc. 8 NA 3 Or C 3 N 2 A 5 Calcium sodium aluminate, calcium lithium aluminate, alumina cement, etc., 3 A 3 ·CaSO 4The calcium aluminates may be crystalline, amorphous, or a mixture of amorphous and crystalline. The calcium aluminates may be used alone or in combination of two or more. The fineness of the calcium aluminates is preferably 3000 cm2 in terms of Blaine specific surface area from the viewpoint of further improving early strength development. 2 / g or more, and 2 / g or more. The fineness of calcium aluminates is preferably 8000 cm2 in terms of Blaine specific surface area. 2 It is preferable that the molecular weight is not more than 1 / g.

[0030] The content of calcium aluminates is preferably 10 to 40 parts by mass, more preferably 15 to 35 parts by mass, and even more preferably 20 to 30 parts by mass, relative to 100 parts by mass of cement. If the content of calcium aluminates is within the above range, the rapid hardening property tends to be more excellent.

[0031] The fiber-reinforced polymer cement mortar composition contains gypsum, which improves the long-term strength development. Examples of gypsum include anhydrous gypsum, hemihydrate gypsum, and dihydrate gypsum. As the gypsum, anhydrous gypsum is preferable from the viewpoint of further improving the strength development. The gypsum may be used alone or in combination of two or more kinds.

[0032] The content of the gypsum is preferably 5 to 30 parts by mass, more preferably 10 to 28 parts by mass, and even more preferably 15 to 25 parts by mass, relative to 100 parts by mass of cement. If the content of the gypsum is within the above range, the long-term strength development is further improved. From the viewpoint of further improving the long-term strength development, the fineness of the gypsum is set to 4500 cm in terms of Blaine specific surface area. 2 / g or more, and 2 / g or more. The fineness of the gypsum is preferably 15,000 cm in terms of Blaine specific surface area. 2It is preferable that the molecular weight is not more than 1 / g.

[0033] The fine aggregate is not particularly limited, and examples thereof include river sand, silica sand, crushed sand, kansui stone, limestone sand, slag aggregate, lightweight aggregate, etc. These fine aggregates may be used alone or in combination of two or more kinds.

[0034] The content of the fine aggregate is preferably 250 to 550 parts by mass, more preferably 300 to 500 parts by mass, and further preferably 350 to 450 parts by mass, relative to 100 parts by mass of cement. When the content of the fine aggregate is within the above range, it is easy to achieve both sufficient compressive strength and splitting tensile strength.

[0035] By including an expansive agent in the fiber-reinforced polymer cement mortar composition, the compressive strength and dimensional change rate of the mortar become excellent. The expansive agent may be any expansive agent that conforms to JIS (JIS A 6202:2008) and is generally used as an expansive agent for concrete. Examples of the expansive agent include an expansive agent mainly composed of free quicklime (quicklime-based expansive agent), an expansive agent mainly composed of auin (ettringite-based expansive agent), and a composite expansive agent of free quicklime and ettringite-forming material. The expansive agent may be used alone or in combination of two or more types. The expansive agent may have a Blaine specific surface area of ​​2000 to 6000 cm. 2 It is preferable to use one having a molecular weight of 1 / g.

[0036] The content of the expansive agent is preferably 0.1 to 5 parts by mass, more preferably 0.5 to 4 parts by mass, and even more preferably 1 to 3 parts by mass, relative to 100 parts by mass of cement. If the content of the expansive agent is within the above range, the compressive strength, dimensional change rate, etc. will be further improved.

[0037] The water reducing agent includes a high-performance water reducing agent, a high-performance AE water reducing agent, an AE water reducing agent, and a superplasticizer. Examples of such water reducing agents include those specified in JIS A 6204:2011 "Chemical admixtures for concrete". Examples of water reducing agents include polycarboxylic acid water reducing agents, naphthalene sulfonic acid water reducing agents, lignin sulfonic acid water reducing agents, and melamine water reducing agents. Among these water reducing agents, polycarboxylic acid water reducing agents are preferred from the viewpoint that the fluidity retention time can be easily ensured even with a small amount of addition. The water reducing agents may be used alone or in combination of two or more types.

[0038] The content of the water reducing agent is preferably 0.1 to 5 parts by mass, more preferably 0.2 to 3 parts by mass, and even more preferably 0.3 to 1 part by mass, relative to 100 parts by mass of cement. If the content of the water reducing agent is within the above range, the pot life is easily ensured and the fluidity is further improved.

[0039] By including a retarder in the fiber-reinforced polymer cement mortar composition, it is easy to ensure a sufficient pot life even when the temperature of the polymer cement mortar is high during the summer or other seasons. Examples of the retarder include organic acids or salts thereof such as citric acid, gluconic acid, malic acid, and tartaric acid; boric acid, borates such as sodium borate, phosphates, alkali metal carbonates, and alkali metal bicarbonates; and sugars. Among these, citric acid, citrates, tartaric acid, tartrates, and alkali metal carbonates are preferred. The retarder may be in the form of a powder or a liquid (for example, an aqueous solution, an emulsion, or a suspension). The retarder may be used alone or in combination of two or more.

[0040] The content of the retarder is preferably 0.1 to 5 parts by mass, more preferably 0.3 to 3 parts by mass, and most preferably 0.5 to 2 parts by mass, relative to 100 parts by mass of cement. If the content of the retarder is within the above range, the pot life is further ensured and the early strength development is less likely to decrease.

[0041] The fiber-reinforced polymer cement mortar composition of the present embodiment may contain various admixtures within the range that does not impair the effects of the present invention. Examples of the admixtures include foaming agents, antifoaming agents, thickeners, waterproofing agents, rust inhibitors, shrinkage reducing agents, water retention agents, pigments, fibers, water repellents, efflorescence inhibitors, quick-setting agents (materials), quick-hardening agents (materials), stone powder, volcanic ash, air entraining agents, and surface hardeners.

[0042] The method for producing the fiber-reinforced polymer cement mortar composition of the present embodiment is not particularly limited, and the composition can be produced, for example, by mixing the above components using a mixer such as a gravity mixer such as a V-type mixer or a tilting concrete mixer, a Henschel mixer, a jet mixer, a ribbon mixer, or a paddle mixer.

[0043] The fiber-reinforced polymer cement mortar composition of the present embodiment can be mixed with water to prepare a fiber-reinforced polymer cement mortar, and the water content may be appropriately adjusted depending on the application. The water content is preferably 20 to 55 parts by mass, more preferably 30 to 52 parts by mass, and even more preferably 35 to 50 parts by mass, per 100 parts by mass of cement. If the water content is within the above range, the kneadability of the metal fiber and the initial and long-term strength development are further improved.

[0044] The fiber-reinforced polymer cement mortar of the present embodiment can be prepared using a kneading tool similar to that used for ordinary mortar compositions, and is not particularly limited. Examples of the kneading tool include a mortar mixer, a hand mixer, a tilting mixer, a biaxial mixer, and a pan mixer.

[0045] The fiber-reinforced polymer cement mortar composition and the fiber-reinforced polymer cement mortar of the present embodiment are high-strength polymer cement mortars, but also have excellent dispersibility of metal fibers. Therefore, they can be suitably used for repair and reinforcement of various structures and sites that require high strength. The construction method is not particularly limited, and can be selected from a method of making a formwork and filling it, a method of applying it with a trowel, a method of spreading it evenly using a vibrator, and the like. EXAMPLES

[0046] The present invention will be described below based on examples, but the present invention is not limited to these.

[0047] [material] Cement (C): High-early-strength Portland cement Pozzolanic material (SF): Silica fume, BET specific surface area: 15m 2 / g Metal fiber 1: Steel fiber, total length: 30 mm, aspect ratio: 45, shape: shape shown in Figure 1(e), proportion of approximately straight parts to total length: 77%, each angle A: 150 degrees Metal fiber 2: Steel fiber, total length: 30mm, aspect ratio: 45, shape: linear · Polymer for cement (P): Styrene butadiene rubber (SBR) emulsion Calcium aluminates: CaO / Al 2 O 3 = 1.4, Vitrification rate: 40%, Blaine specific surface area: 5000 cm 2 / g ·Gypsum: Anhydrite, Brain specific surface area: 7000cm 2 / g Fine aggregate: Silica sand (grain size adjusted) Expansion material: lime-based expansion material, Blaine specific surface area: 3200 cm 2 / g Water reducing agent: Polycarboxylic acid-based high-performance water reducing agent · Retarder: Citric acid

[0048] [Mix design of fiber-reinforced polymer cement mortar composition] The proportions of pozzolanic substance, metal fiber and cement polymer per 100 parts by mass of cement are shown in Table 1, and the mix is ​​designed to contain 28 parts by mass of calcium aluminates, 19 parts by mass of gypsum, 415 parts by mass of fine aggregate, 2 parts by mass of expansive material, 0.8 parts by mass of water reducing agent and 1 part by mass of setting retarder per 100 parts by mass of cement.

[0049] [Table 1]

[0050] [Preparation of fiber-reinforced polymer cement mortar] In an environment of 20°C, water was added to each of the fiber-reinforced polymer cement mortar compositions so that the ratio was 45 parts by mass per 100 parts by mass of cement, and the mixture was mixed with a hand mixer for 120 seconds to produce approximately 3 L of mortar.

[0051] [Evaluation method] Each item was evaluated by the following methods. The evaluation results are shown in Table 2. 1) Fresh properties a) Dispersibility When preparing fiber-reinforced polymer cement mortar using a hand mixer, if the metal fibers were not uniformly dispersed due to the formation of clumps of metal fibers, etc., it was rated as poor (×), and if it was confirmed that the metal fibers were uniformly dispersed, it was rated as good (○). b) Sagging characteristics A concrete slab (300 x 300 x 60 mm) was placed on a 5% gradient, and fiber-reinforced polymer cement mortar was applied to a thickness of 20 mm, smoothed out with a trowel, and the sagging properties were visually observed. Sagging was evaluated as poor (×), and no sagging was evaluated as good (○). 2) Compressive strength The compressive strength was measured at 1 and 28 days of age in accordance with the Japan Society of Civil Engineers standard JSCE-G 5050-2010 "Method of compressive strength test for mortar or cement paste using cylindrical specimens (draft)". The dimensions of the specimen were 50mm in diameter and 100mm in height. The 28-day-old specimens were demolded the following day and cured in water until the age of the specimen. Curing was always performed in a thermostatic chamber at 20℃.

[0052] [Table 2] [Explanation of symbols]

[0053] 10 metal fiber, 1 approximately straight section, 2 deformation section, 3 starting point, 4 end point, A angle

Claims

1. including cement, pozzolanic materials, metal fibers, calcium aluminates, gypsums, and cementitious polymers; the content of the pozzolan substance is 2 to 38 parts by mass, the content of the metal fibers is 2 to 38 parts by mass, the content of the calcium aluminates is 10 to 40 parts by mass, the content of the gypsums is 5 to 30 parts by mass, and the content of the polymer for cement is 0.5 to 18 parts by mass in terms of solid content, relative to 100 parts by mass of the cement; A fiber-reinforced polymer cement mortar composition, wherein the metal fibers have a substantially straight portion and a deformed portion formed by bending at least one end of the metal fibers at an angle of 30 to 160 degrees from the substantially straight portion, the total length of the metal fibers is 25 to 40 mm, and the aspect ratio of the metal fibers is 40 to 65.

2. 2. The fiber-reinforced polymer cement mortar composition according to claim 1, wherein the length of the substantially straight portion accounts for 50 to 95% of the total length of the metal fiber, and the deformed portion is formed by bending each of both ends of the metal fiber so as to form an angle of 30 to 160 degrees with the substantially straight portion.

3. 3. The fiber reinforced polymer cement mortar composition of claim 1 or 2, further comprising an expansive material.

4. The fiber-reinforced polymer cement mortar composition according to any one of claims 1 to 3 and water, The fiber-reinforced polymer cement mortar has a water content of 20 to 55 parts by mass per 100 parts by mass of the cement.

Citation Information

Patent Citations

  • Polymer cement concrete product and production thereof

    JP1991141145A

  • Steel fiber for reinforcing concrete

    JP1993262544A

  • Rotary connector

    JP1995320835A

  • Premixed and high-toughness polymer cement mortar material and high-toughness polymer cement mortar

    JP2007269537A

  • Polymer cement composition

    JP2010105831A